The Role of Green Fiscal Policy in Supporting Green Governance and Green Economic Development - Loso Judijanto; Dzulfikri Azis Muthalib (Pt. Anagata Sembagi Education, 2025)
This article examines the strategic role of green fiscal policy in supporting governance and green economic development in Indonesia. This research uses a descriptive qualitative approach with data collection techniques through semi-structured interviews and documentation studies. The findings indicate that the implementation of green fiscal policy in Indonesia has progressed through instruments such as carbon taxes, green sukuk issuance, and climate budget tagging. These policies not only aim to restructure the fiscal structure towards sustainability but also encourage more transparent, accountable, and collaborative governance. Although still facing challenges such as resistance to reducing fossil fuel subsidies and limited regional capacity, significant opportunities open up through the potential of the national green sector and global financing support. This study concludes that synergy between fiscal instruments, institutional reform, and cross-sectoral governance is key to realizing an inclusive and sustainable green economy.